FAKTOR RISIKO BAYI BERAT LAHIR RENDAH - Nur Annisa; dyah wulan sumekar rw; fidha rahmayani (CV. Jasa Sukses Abadi, 2023)
Low birth weight babies are a preventable health problem in society. This is an important determinant of child survival and development, as well as long-term consequences such as the emergence of non-communicable diseases in their developmental lives. Babies with low birth weigth have a risk of fatality, development and growth delays compared to babies who are not LBW. In general, the causes of LBW are due to maternal and fetal factors, because while in the womb, the fetus receives the supplies it needs to survive from the mother. A large amount of mortality and morbidity can be prevented by addressing the factors associated with low birth weight. The aim of this literature review is to identify risk factors associated with low birth weight. Various studies have shown several risk factors for low birth weight babies, including maternal age during pregnancy and marital status, maternal diet, smoking habits during pregnancy, educational and socio-economic status, maternal activity during pregnancy and history of complications during pregnancy. But of course the existing research still has certain limitations, so further research is needed in the future.